2020
DOI: 10.1080/17474086.2020.1709437
|View full text |Cite
|
Sign up to set email alerts
|

Indirect methods of comparison of the safety of ferric derisomaltose, iron sucrose and ferric carboxymaltose in the treatment of iron deficiency anemia

Abstract: Objectives: The benefits of intravenous (IV) iron greatly outweigh the risks, but IV iron formulations carry a small risk of hypersensitivity reactions (HSRs). The objective was to use standardized Medical Dictionary for Regulatory Activities queries (SMQs) to compare the safety of ferric derisomaltose/iron isomaltoside 1000 (FDI), iron sucrose (IS), and ferric carboxymaltose (FCM) using prospective trial data. Methods: Prospective trials reporting the incidence of SMQ-coded serious or severe HSRs were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
1
36
0
1
Order By: Relevance
“…Aside from ferric gluconate, none of the IV iron products included in this previous analysis had a statistically significant increase in severe infusion reactions compared to any comparator 19 . Additionally, a recent comprehensive meta‐analysis of 21 prospective, regulatory‐standard clinical trials in 8599 patients with iron deficiency anemia receiving FDI, FCM, or IS found rates of serious or severe HSRs (defined using standardized MedDRA terms) to be low and similar to those in our analysis 20 . A lack of understanding of the true nature of minor acute infusion reactions and their management has resulted in the misperception that IV iron products are associated with a high risk of severe HSRs.…”
Section: Discussionsupporting
confidence: 83%
“…Aside from ferric gluconate, none of the IV iron products included in this previous analysis had a statistically significant increase in severe infusion reactions compared to any comparator 19 . Additionally, a recent comprehensive meta‐analysis of 21 prospective, regulatory‐standard clinical trials in 8599 patients with iron deficiency anemia receiving FDI, FCM, or IS found rates of serious or severe HSRs (defined using standardized MedDRA terms) to be low and similar to those in our analysis 20 . A lack of understanding of the true nature of minor acute infusion reactions and their management has resulted in the misperception that IV iron products are associated with a high risk of severe HSRs.…”
Section: Discussionsupporting
confidence: 83%
“…5 Furthermore, a recent indirect comparison of serious and severe hypersensitivity reactions (HSRs) after administration of IV iron found that, while rates were low regardless of the iron formulation used, the incidence was significantly high with FDI than with FCM. 22 Across the two US pivotal RCTs used for regulatory approval of FCM in the US (N=1775), the incidence was 1.46% (based on 26 events), versus 0.58% with FDI based on 22 events in 3775 patients enrolled in 16 prospective studies of FDI. 23 Future modeling analyses could therefore also capture the incidence of hypophosphatemia and HSRs as potential clinical and economic differentiators between the two iron formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for teratogenic or foeto-toxic effects is considered minimal at the proposed therapeutic dose. Several studies of FDI treatment of iron deficiency anaemia have been published without detected unexpected safety issues [25][26][27][28][29][30][31]. FDI should be confined to second and third trimester if the benefit is judged to outweigh the potential risk for both the mother and the foetus [6,32,33].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%